2009
DOI: 10.3174/ajnr.a1714
|View full text |Cite
|
Sign up to set email alerts
|

A Radiologic Score to Distinguish Autoimmune Hypophysitis from Nonsecreting Pituitary Adenoma Preoperatively

Abstract: BACKGROUND AND PURPOSE:Autoimmune hypophysitis (AH) mimics the more common nonsecreting pituitary adenomas and can be diagnosed with certainty only histologically. Approximately 40% of patients with AH are still misdiagnosed as having pituitary macroadenoma and undergo unnecessary surgery. MR imaging is currently the best noninvasive diagnostic tool to differentiate AH from nonsecreting adenomas, though no single radiologic sign is diagnostically accurate. The purpose of this study was to develop a scoring sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 45 publications
4
121
1
9
Order By: Relevance
“…Gutenberg et al 14 reported that these findings contributed significantly to classifying the outcome as pituitary adenoma or autoimmune hypophysitis (including lymphocytic and granulomatous hypophysitis), and our results were consistent with their findings. 14 Although MR imaging findings such as loss of PPHI, thickened stalk, pituitary symmetry, and homogeneous enhancement showed significant difference in the statistical analysis in the present study, these findings were nonspecific and were observed in both diseases. Loss of PPHI was observed in central diabetes insipidus due to idiopathic, inflammatory, or neoplastic processes, including pituitary adenoma.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Gutenberg et al 14 reported that these findings contributed significantly to classifying the outcome as pituitary adenoma or autoimmune hypophysitis (including lymphocytic and granulomatous hypophysitis), and our results were consistent with their findings. 14 Although MR imaging findings such as loss of PPHI, thickened stalk, pituitary symmetry, and homogeneous enhancement showed significant difference in the statistical analysis in the present study, these findings were nonspecific and were observed in both diseases. Loss of PPHI was observed in central diabetes insipidus due to idiopathic, inflammatory, or neoplastic processes, including pituitary adenoma.…”
Section: Discussionsupporting
confidence: 83%
“…Some previous studies reported that loss of PPHI, thickened stalk, pituitary symmetry, homogeneous enhancement, and the dural tail were useful for distinguishing LYH from pituitary adenomas, 2,3,8,[11][12][13][14] but only 1 previous study investigated this statistically. Gutenberg et al 14 reported that these findings contributed significantly to classifying the outcome as pituitary adenoma or autoimmune hypophysitis (including lymphocytic and granulomatous hypophysitis), and our results were consistent with their findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 All patients diagnosed with autoimmune hypophysitis were followed every three monthly with evaluation for pituitary functions and six monthly with gadolinium enhanced MRI of pituitary. At diagnosis all patients were evaluated with automated perimetry; if found abnormal automated perimetry was repeated every month till normalisation of visual fields.…”
Section: Methodsmentioning
confidence: 99%